2007
DOI: 10.1016/j.nurt.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Spinocerebellar Ataxia Type 6

Abstract: Summary: Spinocerebellar ataxia type 6 (SCA6) is a neurodegenerative disorder caused by abnormal expansions of a trinucleotide CAG repeat in exon 47 of the CACNA1A gene, which encodes the ␣1A subunit of the P/Q-type voltage-gated calcium channel. The CAG repeat expansion is translated into an elongated polyglutamine tract in the carboxyl terminus of the ␣1A subunit. The ␣1A subunit is the main pore-forming subunit of the P/Q-type calcium channel. Patients with SCA6 suffer from a severe form of progressive atax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 102 publications
1
41
0
Order By: Relevance
“…For example, in SCA6, the small polyQ expansions seen in the affected protein, the alpha subunit of the P/Qvoltage gated calcium channel, affect channel function (Kordasiewicz and Gomez 2007). The relative contribution of impaired channel function and polyQ toxicity to SCA6 pathology is still the subject of some debate (Kordasiewicz and Gomez 2007).…”
Section: Open Reading Frame Expansionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in SCA6, the small polyQ expansions seen in the affected protein, the alpha subunit of the P/Qvoltage gated calcium channel, affect channel function (Kordasiewicz and Gomez 2007). The relative contribution of impaired channel function and polyQ toxicity to SCA6 pathology is still the subject of some debate (Kordasiewicz and Gomez 2007).…”
Section: Open Reading Frame Expansionsmentioning
confidence: 99%
“…For example, in SCA6, the small polyQ expansions seen in the affected protein, the alpha subunit of the P/Qvoltage gated calcium channel, affect channel function (Kordasiewicz and Gomez 2007). The relative contribution of impaired channel function and polyQ toxicity to SCA6 pathology is still the subject of some debate (Kordasiewicz and Gomez 2007). Small increases in the number of glutamines are also associated with a reduced transactivation ability of the androgen receptor (Mhatre et al 1993;Chamberlain et al 1994).…”
Section: Open Reading Frame Expansionsmentioning
confidence: 99%
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
“…Onset generally occurs in the fifth decade of life and lifespan is not shortened [108,109]. Neurodegeneration occurs selectively in the PCs of the cerebellum with no neuropathy in other neurons, making it a pure cerebellar ataxia [110]. Unlike other polyQ diseases, only certain isoforms of Ca v 2.1 contain the expanded glutamine tract [111,112].…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%